2016
DOI: 10.18466/cbujos.70961
|View full text |Cite
|
Sign up to set email alerts
|

Et Ürünlerinde Nitrat ve Nitrit Kullanımına Potansiyel Alternatif Yöntemler

Abstract: Nitrat ve nitrit et ürünlerinde; karakteristik renk ve lezzetin gelişimine katkıda bulunması, lipid oksidasyonunu kontrol altına alması ve başta Clostridium botulinum olmak üzere patojen mikroorganizmalar üzerine antimikrobiyal etki göstermesi nedenleriyle yaygın olarak kullanılmaktadır. Ancak bu katkılar, alım dozu, sıklığı ve şekline bağlı olarak akut ve kronik zehirlenmelere yol açarak insan sağlığı açısından risk oluşturmaktadırlar. Nitrat ve nitrit tek başına kanserojen olmayıp, pişirme veya sindirim sıra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Since nitrate/nitrite has various functions in meat, no single additive that could fulfill all these functions could be found. Besides decreasing or preventing the use of nitrite in meat products by making use of natural elements, organic acids, irradiation, pressure applications, and hazard technology were also investigated in the previous studies (Turp & Sucu, 2016).Thyme is an important herb, thanks to its high thymol concentration. Previous studies revealed the anti-oxidative, antimi-…”
mentioning
confidence: 99%
“…Since nitrate/nitrite has various functions in meat, no single additive that could fulfill all these functions could be found. Besides decreasing or preventing the use of nitrite in meat products by making use of natural elements, organic acids, irradiation, pressure applications, and hazard technology were also investigated in the previous studies (Turp & Sucu, 2016).Thyme is an important herb, thanks to its high thymol concentration. Previous studies revealed the anti-oxidative, antimi-…”
mentioning
confidence: 99%
“…Et ürünlerinde kullanılan nitrit ve kalıntı nitrit miktarının azaltılması, bitkisel kaynaklı doğal katkıların, organik asitlerin, mikrobiyal kaynakların kullanımı, ışınlama, yüksek basınç ve engel teknolojisi uygulamaları ile sağlanabilmektedir [56,62]. Bileşimlerinde doğal olarak nitrat içeren bitkisel kaynaklı katkıların yaygın olarak kullanımı söz konusudur [63,64].…”
Section: Fermente Sosi̇slerde Ni̇tri̇t Alternati̇fi̇ Katkilarunclassified
“…5,7 For this reason, safety data, such as acceptable daily intake, based on toxicological studies on experimental animals and human clinical studies have been determined and evaluated by the Food and Agricultural Organization and World Health Organization. [8][9][10] In view of these concerns, there have been many researchers across the earth evaluating the fate and removal of these contaminants in wastewater treatment processes as the classical treatment procedures are not efficient in removing the chemicals to levels below their potentially no effect concentrations. 11,12 Because of economic and technical drawbacks, sunset yellow FCF recycling and removal technologies have not yet been widely adopted.…”
Section: Introductionmentioning
confidence: 99%